1991
DOI: 10.1042/bj2800471
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of cephalosporin 7α-hydroxylase from Streptomyces clavuligerus

Abstract: Cephalosporin 7 alpha-hydroxylase, which catalyses the conversion of cephalosporins into their 7 alpha-hydroxy derivatives, was purified nearly 390-fold from Streptomyces clavuligerus through ion-exchange chromatography, (NH4)2SO4 fractionation, gel filtration and dye chromatography, with the use of h.p.l.c. to monitor enzyme activity. The nearly pure enzyme migrates as a single major band, with an Mr of 32,000 in SDS/PAGE. Its optimum pH is in the range 7.3-7.7. Under our conditions the reaction was fastest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In Cephalosporium acremonium a single, bifunctional protein, deacetoxy/deacetylcephalosporin C synthase (DAOC/DAC synthase), performs both reactions (2)(3)(4). S. clavuligerus also contains a 7␣-hydroxylase, which is involved in the biosynthesis of cephamycin C from DAC (5).…”
Section: Deacetoxycephalosporin C Synthase (Daocs)mentioning
confidence: 99%
“…In Cephalosporium acremonium a single, bifunctional protein, deacetoxy/deacetylcephalosporin C synthase (DAOC/DAC synthase), performs both reactions (2)(3)(4). S. clavuligerus also contains a 7␣-hydroxylase, which is involved in the biosynthesis of cephamycin C from DAC (5).…”
Section: Deacetoxycephalosporin C Synthase (Daocs)mentioning
confidence: 99%
“…Initial evidence showed that P7 and P8 copurify after Blue Sepharose (Pharmacia) purification. Xiao et al (21) reported the purification of a major protein band (32 kDa) that correlated with 7␣-hydroxylase activity. A second band with a slightly lower molecular mass was seen in their gels after Blue Sepharose purification.…”
Section: Characterization Of Orf7 and Orf8mentioning
confidence: 99%
“…In summary, P7 is required for hydroxylase activity and may be equivalent to the 32-kDa protein isolated by Xiao et al (21). Importantly, we have found another coding sequence (ORF8) that, when present with ORF7 in S. lividans, yields methoxylated cephalosporin C. Molecular genetic evidence and preliminary biochemical evidence indicate that P7 and P8 are necessary for efficient methoxylation of cephalosporin; the methoxylation system is also reminiscent of a two-component hydroxylase, such as the p-hydroxyphenylacetate-3-hydroxylase from P. putida that includes a flavoprotein with substrate-stimulated NADH oxidase (P7) and a coupling protein (P8) that is crucial for coupling and hydroxylation of the substrate.…”
Section: Characterization Of Orf7 and Orf8mentioning
confidence: 99%
“…The first step is the hydroxylation of cephalosporin at C-7, and the second step is methylation. Cephalosporin 7a-hydroxylase (CH), which catalyzes the first step, was purified to near homogeneity from S. clavuligerus NRRL 3585 (19). In the present study, using a degenerate mixed-oligonucleotide probe designed * Corresponding author.…”
mentioning
confidence: 99%
“…The flasks were incubated on a rotary shaker (30°C, 250 rpm) for 3 days. The mycelium was collected by centrifugation (15 min, 2,200 x g) to prepare cell extracts for analysis of CH enzymatic activity as described previously (18,19). The activity was measured by a high-performance liquid chromatography (HPLC) assay which detected the formation of 7at-hydroxycephalosporin C (HCPC) from the substrate cephalosporin C (CPC) in a cell-free enzymatic reaction.…”
mentioning
confidence: 99%